A density functional theory investigation on the formation mechanisms of DNA interstrand crosslinks induced by chloroethylnitrosoureas. Issue 9 (16th July 2012) - Zhao, Li‐Jiao; Ma, Xin‐Yan; Zhong, Ru‐Gang
Abstract Chloroethylnitrosoureas (CENUs) are an important family of alkylating agents used in the clinical treatment of cancer. Their anticancer mechanism primarily involves the formation of DNA interstrand crosslinks (ICLs) induced by the chloroethyldiazonium ion derived from the decomposition of CENUs. In this work, the mechanism for the formation of ICLs was investigated by density functional theory (DFT) with B3LYP, wB97XD, and M062X functinoals using conductor‐like polarizable continuum model solvent model. Three pathways leading to the formation of three types of G–C crosslinks were compared. G(N1)–C(N3) crosslink is predicted to be the dominant crosslinking product other than G(O6)–C(N4) and G(N2)–C(O2) crosslinks, which is consistent with the previous results obtained from QM/MM computations. The results indicate that the formation of the G(N1)–C(N3) crosslink via pathway A is the most favorable mechanism from both kinetic and thermodynamic standpoints. In this pathway, the chloroethyldiazonium ion alkylates guanine on the O6 site followed by intramolecular cyclization to form O6, N1‐ethanoguanine (4). The cytosine then reacts with intermediate 4 on the Cα atom to yield the G(N1)–C(N3) crosslink. This work provides reasonable explanations for the supposed mechanism of CENUs‐induced ICLs formation obtained from experimental investigations. © 2012 Wiley Periodicals, Inc.